Temporal Changes of Spinal Transcriptomic Profiles in Mice With Spinal Nerve Ligation - Yu, Hong; Zhang, Piao; Chen, Ye-Ru; Wang, Yong-Jie; Lin, Xian-Yi; Li, Xiang-Yao; Chen, Gang (Frontiers in Neuroscience, 2019)
Neuropathic pain (NP) is an intractable disease accompanying with allodynia, hyperalgesia and spontaneous pain. Accumulating evidence suggested that large volume of neurotransmitters, genes, and signaling pathways were implicated with the initiation and development of NP, while the underlying mechanism still remained poorly understood. Therefore, it was extremely important to further elucidate the potential regulatory networks for developing appropriate treatment options. Here, the RNA-seq high-throughput sequencing was employed to determine the genes expression change in mice undergoing spinal nerve ligation (SNL). Meanwhile, the differentially expressed genes (DEGs) were analyzed by using integrated Differential Expression and Pathway analysis (iDEP) tools and String database. Then, quantitative real-time PCR (qRT-PCR) was employed to detect the expression of hub gens. The results showed that the DEGs mainly comprised 1712 upregulated and 1515 downregulated genes at 7d, and consisted of 243 upregulated and 357 downregulated genes at 28d after surgery, respectively. Additionally, 133 genes and two pathways including retrograde endocannabinoid signaling and cardiac muscle contraction collectively participated in biological reactions of 7th and 28th day after operation. Moreover, the results showed that the expression of CCL5, Cacna2d1, Cacna2d2, Cacnb2, Ccl21a, Gabrb3, GluA1, and GluA2 was significantly higher in SLN-7/28d group than that of in Sham-7/28d group (SLN-7d VS Sham-7d; SLN-28d VS Sham-28d; P<0.05). And the level of Glra2, Glra4, Glra3, Grik1, Grik2, NR1, NR2A and NR2B was obviously increased in SLN-7d group compared to Sham-7d group (P<0.05), but which was no statistical difference between SLN-28d group and Sham-28d group. Therefore, these results provided new perspectives and strategies for deeply illuminating the underlying mechanism, and identifying the key elements for treating NP.